Pipe Dream Publicity Still - David Allen:::Creator::::::::::::
A picture promoting the 42nd Street Moon's 'Lost Musical' Series "Pipe Dream," which is based on Cannery Row. On the left, a Monterey madam, Fauna (Pat Christensen,) teaches Suzy (Beth Wilmurt) the secrets of ladylike elegance. It was played at New Conservatory Theatre.